Kebijakan Non Penal untuk Menekan Tindak Pidana Narkotika Melalui Double Track System - Januar Rahadian Mahendra (Faculty of Law, Maranatha Christian University, 2024)
This research will analyze the problems contained in the implementation of the double track system for narcotics crimes using Lawrence M. Friedman's legal system theory. The author uses normative legal research with a conceptual approach and deductive method accompanied by supporting data to produce a comprehensive and critical analysis to answer the problem. The purpose of this research is to find problems in the use of the double track system in narcotics crimes using Friedman's legal system theory, this is done because in Friedman's legal system theory will divide through three aspects, namely legal substance, legal structure, and legal culture in narcotics crimes. Based on the results of the research, the legal substance problem in narcotics crime is the existence of strict liability which can cause overcriminalization so that depenalization, decriminalization, and diversion policies are needed in the Narcotics Law. In addition, there is a tendency for judges in deciding narcotics cases to only use imprisonment without accompanying it with rehabilitation. In the legal structure, there are problems in the form of a lack of drug rehabilitation facilities, the strong retributive influence so that imprisonment is the main answer in dealing with problems, abuse of power committed by law enforcers, and imprisonment which is a criminogenic factor for narcotics crimes. While the problems in legal culture are stigmatization by the community, the need for confidentiality of identity, the influence of the surrounding environment, and the level of education and employment affect the incidence of drug crimes.